Incidence And Characteristics Of Double Lumen Induced Central Venous Catheter-Related Thromboembolism In Hemodialytic Patients - Tjiang, Margaret Merlyn; Prayoga, Dimas Arsana (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Background: Central venous catheters (CVCs) are frequently used in patients for several indications such as cancer treatment, diagnostic monitoring, parenteral nutrition, hemodialysis, and administration of fluids, blood products or medication. Double lumen catheter induced CVCs thrombosis has not been paid into proper attention in developing countries such as Indonesia.Aims: The aim of this study is to identify the incidence and characteristic of double lumen catheter induced CVCs thrombosis in patients undergoing hemodialysis.Methods: This systematic review has been registered in PROSPERO (CRD42020181584). A systematic search of literature for observational and randomized controlled trial was conducted in PubMed, PubMed central, and Google Scholar through April 16, 2020. Two reviewers independently searched and selected. The risk of bias was evaluated using the Newcastle-Ottawa Quality assessment tool. Results: A total of 408 patients were included in our study. There were 192 (47.1%) male patients. The double lumen catheter was mostly placed in the jugular vein (60%), followed by subclavian vein (25%) and femoral vein (15%). Four (1.1%) patients had deep vein thrombosis after about one month of double lumen catheter placement. All these four patients, the double lumen catheter was inserted in the femoral vein. Any other significant risk factors for thrombosis other than double lumen catheter insertion not found. Out of these four patients, one of them passed away. All patients were treated using heparin.Conclusion: The incidence of double lumen catheter induced thrombosis is low (1.1%) in patients undergoing hemodialysis. However, further larger study is needed to confirm and find the associating factors.